Bread baking and its color kinetics modeled by the spatial reaction engineering approach (S-REA). (May 2015) - Putranto, Aditya; Chen, Xiao Dong; Zhou, Weibiao
Abstract: Baking is a relatively complex process involving simultaneous heat and mass transfer coupled with reactions and structural changes. An accurate and physically-meaningful model of baking is useful to assist process design and product quality improvement. The reaction engineering approach (REA), which has been proven to accurately model the drying rate of porous foods, is implemented here to describe the local evaporation/condensation rate during bread baking for the first time. The REA is coupled with a set of equations of conservation of heat and mass transfer to yield the spatial reaction engineering approach (S-REA). The results of modeling match well with the experimental data. The S-REA can also model the browning kinetics during bread baking accurately. The S-REA is readily implemented for process design by implementing it in computational fluid dynamics (CFD)-environment. The S-REA can also be used for optimization to determine baking trajectories to achieve the desired product properties. Highlights: The S-REA is developed to model bread baking process. The S-REA is accurate to model bread baking and the surface color kinetics. The S-REA is an effective non-equilibrium multiphase heat and mass transfer model. The S-REA can assist in maintaining the product quality during baking.